2013
DOI: 10.1186/1471-2458-13-926
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and related health risk behaviours among school learners in South Africa: results from the 2002 and 2008 national youth risk behaviour surveys

Abstract: BackgroundAttempted and completed suicide constitute a major public health problem among young people world-wide, including South Africa (SA). Suicide attempt and completed suicide increase during the adolescent period. One in 5 adolescents considers attempting suicide, but statistics are frequently unreliable.MethodsData for this study were derived from the 2002 and 2008 South African Youth Risk Behaviour Surveys (YRBS). The study population comprised grades 8, 9, 10 and 11 students in governmental schools in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 41 publications
7
48
0
Order By: Relevance
“…In fact, in one study, the methods of attempted suicide were hanging or gunshot for seven out of ten boys and drug overdose for nine out of ten girls [15]. By contrast, more women attempt suicide than men [16, 17]. However, women tend to use less effective and gentler methods in their suicide attempts than men, which less frequently require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in one study, the methods of attempted suicide were hanging or gunshot for seven out of ten boys and drug overdose for nine out of ten girls [15]. By contrast, more women attempt suicide than men [16, 17]. However, women tend to use less effective and gentler methods in their suicide attempts than men, which less frequently require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Poland that assessed suicide attempts by various methods showed that the most common method was intoxication with medical drugs (42.31 %) [16]. In a review of methods used to commit suicide in Asia, hanging and poisoning with solid/liquid substances (mainly pesticides) were the predominant methods [33].…”
Section: Discussionmentioning
confidence: 99%
“…While suicide risk has been understudied in sub-Saharan Africa (SSA), there is some evidence to suggest that rates of suicidal ideation and attempt might be higher among individuals living in SSA, with studies finding rates of suicidal behavior among school children ranging from 19.6% in Uganda to a high of 31.9% in Zambia (4). One study in South Africa found that more than one in five adolescents ages 13–19 reported having attempted suicide in the last six months (5). These observed elevated rates of suicidal ideation and behavior in youth in SSA may be due in part to disproportionately high rates of stressors with known associations to suicidality, such as HIV, which has been observed to increase psychosocial stress and hopelessness (68).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that given the limited resources of public health systems, school resources should be used to develop evidence-based suicide prevention and intervention programmes (e.g., Shilubane et al, 2013; Peltzer, Kleintjies, van Wyk, Thompson, & Mashego, 2008) with school personnel, such as teachers, being involved in screening for a national suicide prevention programme to become fully established (Schlebusch, 2012). …”
mentioning
confidence: 99%
“…Another measure used in South Africa is the Youth Risk Behavior Survey (YRBS) developed by the Youth Risk Behavior Surveillance System in the United States for the Centers for Disease Control and Prevention. The YRBS has been adapted by Shilubane and colleagues (2013). However, little research has been done in this area and most of this work has been largely descriptive (e.g., Wild, Flisher, & Lombard, 2004).…”
mentioning
confidence: 99%